Limited influence of Si on the preservation of Fe mineral‐encrusted microbial cells during experimental diagenesis. Issue 3 (23rd December 2015) - Picard, A.; Obst, M.; Schmid, G.; Zeitvogel, F.; Kappler, A.
Abstract: The reconstruction of the history of microbial life since its emergence on early Earth is impaired by the difficulty to prove the biogenicity of putative microfossils in the rock record. While most of the oldest rocks on Earth have been exposed to different grades of diagenetic alterations, little is known about how the remains of micro‐organisms evolve when exposed to pressure (P) and temperature (T) conditions typical of diagenesis. Using spectroscopy and microscopy, we compared morphological, mineralogical, and chemical biosignatures exhibited by Fe mineral‐encrusted cells of the bacterium Acidovorax sp. BoFeN1 after long‐term incubation under ambient conditions and after experimental diagenesis. We also evaluated the effects of Si on the preservation of microbial cells during the whole process. At ambient conditions, Si affected the morphology but not the identity (goethite) of Fe minerals that formed around cells. Fe‐encrusted cells were morphologically well preserved after 1 week at 250 °C‐140 MPa and after 16 weeks at 170 °C‐120 MPa in the presence or in the absence of Si. Some goethite transformed to hematite and magnetite at 250 °C‐140 MPa, but in the presence of Si more goethite was preserved. Proteins—the most abundant cellular components—were preserved over several months at ambient conditions but disappeared after incubations at high temperature and pressure conditions, both in the presence and in the absence of Si. Other organic compounds, such as lipids and extracellular polysaccharides seemed well preserved after exposure to diagenetic conditions. This study provides insights about the composition and potential preservation of microfossils that could have formed in Fe‐ and Si‐rich Precambrian oceans.